1999
DOI: 10.1136/jnnp.67.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hu antibody titre and brain metastases before and after treatment for small cell lung cancer

Abstract: (J Neurol Neurosurg Psychiatry 1999;67:353-357)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
28
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 8 publications
9
28
0
4
Order By: Relevance
“…42 A higher proportion of females among seropositives compared with seronegatives has also been reported for Hu antibodies. 38 Parallel to our findings that anti-SOX1/ZIC2 double-positive patients and high-titer SOX1-seropositive patients are often associated with better clinical parameters, studies of anti-Hu antibodies also showed high titers or coexistence of anti-Hu and anti-ZIC4, and anti-CRMP-5 antibodies to closely associate with autoimmune PND. 20,24 This indicates that high-titer antibody and/or responses against multiple antigens are likely to reflect a more effective immune response, which may result in a better tumor prognosis as well as in the development of PND in the case of some antigens.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…42 A higher proportion of females among seropositives compared with seronegatives has also been reported for Hu antibodies. 38 Parallel to our findings that anti-SOX1/ZIC2 double-positive patients and high-titer SOX1-seropositive patients are often associated with better clinical parameters, studies of anti-Hu antibodies also showed high titers or coexistence of anti-Hu and anti-ZIC4, and anti-CRMP-5 antibodies to closely associate with autoimmune PND. 20,24 This indicates that high-titer antibody and/or responses against multiple antigens are likely to reflect a more effective immune response, which may result in a better tumor prognosis as well as in the development of PND in the case of some antigens.…”
supporting
confidence: 70%
“…Anti-Hu antibody titers have also been reported to remain detectable over the course of disease, except in patients who had complete elimination of cancer after therapy, for whom titers decreased rapidly and in parallel to a loss of paraneoplastic neurologic symptoms. 38,47 Similar observations correlating antibody titers to tumor burden have been observed for the CT antigen NY-ESO-1. 48 However, tumor presence, rather than tumor burden, seems to be associated with SOX/ZIC2 antibodies because they are more frequently observed in patients with limited-stage disease and are associated with lower LDH levels.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Although the follow-up period was short and only a few controls were used, Tsou et al reported that SCLC patients with high levels of anti-Hu reactivity survived for longer than those with low levels (p=0.08) (32). In agreement with the study by Tsou et al and the present study, Verschuuren et al also reported that anti-Hu-positive SCLC cases survived longer, and Dalmau et al reported that anti-Hu-positive SCLC patients have relatively limited disease (29,33). Larger scale studies are need to classify the reason for the favorable prognosis of SCLC patients with anti-Hu autoantibodies.…”
Section: Discussionsupporting
confidence: 82%
“…p53 antikorunun tümör dokusu ile savaşan bir immün yanıtın göstergesi olduğunu düşünürsek Tablo 3 ve 4'de özetlenen bilgiler ışığında, kişinin kanserine karşı savaşını kazanması halinde bu savaşın göstergesi (ve belki silahları) olan anti-tümör antikorlarının da serumdan kaybolduğunu, savaşın kazanılama-dığı durumlarda ise, müteakip yıllarda kanda böyle antikorların idame ettiğini düşünebiliriz. Bunu destekleyen diğer bir grup veri ise aynı sorunun tersten sorulmasıyla elde edilmiştir: Tümöre karşı gelişen antikor yanıtlarının tümörün kemoterapi veya cerrahi müdaha-le ile tedavi edilmesi halinde ortadan kalktığı görülmüş-tür (15,16). Diğer bir deyişle, savaş sebebi olan hücre-ler ortadan kalkınca, savaşın göstergesi olan antikorlar da kaybolmaktadır.…”
Section: Kanserle Immün Sistemin Savaşıunclassified